Aspectos del léxico en la juventud chalaca: campos léxico y estructura radial - Ochoa Madrid, Jasmin (2021)
El presente estudio es una aproximación a la construcción del significado de dos estructuras lexicales muy recurrentes en el sociolecto del Callao: choque y fuga y amigos con derecho.  En un inicio, mediante la matriz estructural de rasgos semánticos, se arribó a la elaboración del significado de estas dos estructuras lexemáticas de una manera rigurosa pero inexacta con respecto a la realidad. Teniendo en cuenta que la mente humana es muy imaginativa y esta va en consonancia con el creativo uso del lenguaje utilizamos la estructura de las redes semánticas radiales para llegar a una mejor representación cognitiva construida por los hablantes, lo que se verbaliza en un discurso.   ABSTRACT The current study is an approximation of the construction of the meaning of two lexical structures very recurrent in the sociolect of Callao: choque y fuga y amigos con derecho. Initially, through the structural matrix of semantics features was reached on the development of the meaning of these two lexical structures in a rigorous manner but inaccurately regarding the reality. Considering that the human mind is extremely imaginative and it´s in line with the creative uses of the language, we use the structure of radials semantic network to achieve a better cognitive representation constructed by the speakers, of what is verbalized in a basilectal discourse. Within the framework of the cognitive sciences, the lexical structures frequently used which are by polysemic nature, thus, they acquire different meanings. From the central nodes irradiate semantically new and different meanings. On that basis, we can conclude that the linguistic intuitions the speakers have can become into intelligible with help of the cognitive basis metalanguage.